AuPd/C core-shell and alloy nanoparticles with enhanced catalytic activity toward the electro-oxidation of ethanol in alkaline media - Silva, Lays S. R.; Almeida, Caio V. S.; Meneses, Cristiano T.; Batista, Elizete A. [UNESP]; Santos, Sydney F.; Eguiluz, Katlin I. B.; Salazar-Banda, Giancarlo R. (Elsevier B.V., 2019)
Carbon-supported Pd, Au@Pd core-shell and Au1-xPdx-alloyed nanoparticles were prepared by a chemical reduction method and characterized by different experimental techniques, including X-ray powder diffraction, transmission electron microscopy, scanning-transmission electron microscopy using bright-field and high-angle annular dark field detectors and X-ray energy dispersive spectroscopy. The catalytic mass activity toward ethanol oxidation was assessed by cyclic voltammetry and chronoamperometry at room temperature. The measurements showed that the addition of Au enhances remarkably the electrocatalytic activity of the material, due to the bifunctional effect of Au1-xPd/C alloys, and the synergetic effect on Au@Pd/C, resulting in a dissolution resistance of core-shell catalysts at potentials of 1.5 V versus reversible hydrogen electrode. In situ Fourier transform infrared spectroscopy measurements showed that the mechanism for ethanol oxidation depends on the electrocatalyst structure and morphology. Acetate was identified as the main product of ethanol electro-oxidation on the studied electrocatalysts. However, the presence of a core-shell structure on Au@Pd/C resulted in enhanced ethanol oxidation selectivity toward CO2. The improvement of activity is attributed to the interaction between Pd shell and Au core.
Keywords: Core shell nanostructures; PdAu-based electrocatalysts; Ethanol electro-oxidation; Scanning-transmission electron microscopy; Fuel cells